Adherence to treatment of osteoporosis in postmenopausal patients in a referral hospital, Peru 2013 - Tejada Llacsa, Paul Jesús (2015)
Introduction: Despite the efficacy of treatment for osteoporosis, about 50% of the patients tend to discontinue. Objectives: To assess the frequency of poor adherence to treatment of osteoporosis and its associated characteristics. Design: A descriptive, cross-sectional study. Location: Department of Rheumatology, National Hospital Alberto Sabogal, Callao, Peru. Participants: Patients diagnosed with postmenopausal osteoporosis. Interventions: In February and March 2013 a questionnaire of 32 questions to postmenopausal women with osteoporosis was applied. The Morisky-Green (MG) was used to measure adherence to treatment. Main outcome measures: Percentage and characteristics associated with nonadherence. Results: 81 patients were surveyed; the mean age was 67.1 years (± 8.2); the percentage of non-adherence to treatment was 80.2%. Associated features were number of additional medications, number of comorbidities, diabetes and lack of seeking information about the disease. Conclusions: There is a high percentage of non-adherence to osteoporosis, so we suggest future studies to characterize this problem in our context.